Nilai Nutrien dan Kecukupan WSC Berbagai Hijauan Sebagai Sumber Pakan Silase - Rodiallah, Muhamad; Harahap, Anwar Efendi; Ali, Arsyadi; Adelina, Triani; Mucra, Dewi Ananda; Solfan, Bakhendri; Juliantoni, Jepri; Misrianti, Restu; Irawati, Evi; Saleh, Eniza; Mulia, Fungki Firma; Noviana, Riskia (Unpad Press, 2023)
Cultivation of forages from graminae and legumes is an alternative source of fiber feed to meet basic living needs and ruminant livestock production. This research aims to assess the nutritional and WSC content of various forages as indicators and considerations in making silage. The research used a completely randomized design with 5 treatments with 4 replications. Regarding the treatment of forage types, namely A = elephant grass; B = Gama Umami; C= Mexican Grass; D= Odot grass; D = Indigofera beans. The research parameters are crude protein (%), crude fat (%), dry matter (%), ash, crude fiber (%), water-soluble carbohydrates (%), and NDF and ADF content (%). The results showed that different types of forage had a significant effect (P<0.05) on the nutritional value and WSC content. The research conclusion was that Indigofera legumes and odot grass had the highest WSC content, namely 4.59% and 4.49%. Furthermore, indigofera legumes and odot grass also produce the lowest NDF and ADF values compared to other treatments, so they have the potential to be used as raw materials for making silage to support the availability of ruminant feed